The Impact of Prenatal Parental Locus of Control on Children's Psychological Outcomes in Infancy and Early Childhood: A Prospective 5 Year Study - Nowicki, Stephen; Iles-Caven, Yasmin; Gregory, Steven; Ellis, Genette; Golding, Jean (Frontiers in Psychology, 2017)
Locus of control is one of the most widely studied concepts in the history of personality psychology. In spite of its popularity and its associations with numerous relevant outcomes, the ability of locus of control to predict future behaviors involving parenting effectiveness has been under researched. The few parent locus of control, children’s outcome studies are characterized by cross-sectional methodologies that focus on mothers. The present study uses a prospective methodology to compare data on mothers’ and fathers’ locus of control with their child outcomes from a large scale research project, the Avon Longitudinal Study of Parents and Children (ALSPAC). Based on Rotter’s Social Learning Theory published in 1954 and past empirical research it was predicted and found that parent internality was associated with more positive child outcomes than parent externality. More specifically, when both parents were internal, their children had more positive outcomes in sleeping, eating, and tantrum behavior as compared to any other parent locus of control combination. Results confirmed how important parent locus of control is in the lives of children. Based on the findings, researchers are urged to develop interventions to change advice to parents and promote more internal locus of control among parents.